Possibilities and prospects for the development of integrated digitalization at the motor transport enterprise - Martynushkin Aleksey; Lozovaya Oksana (E3S Web of Conferences, 2023)
Modern opportunities for introducing digital technologies for enterprises of all industries in the Russian Federation are constrained by the fact that most software products have been developed for certain areas of functional blocks of work: corporate document management systems (with weak industry-specific support in relation to vehicles), accounting, finance and credit, personnel records management. With the displacement of management links by digital points for collecting, analyzing, evaluating and solving problems of optimizing routes, cost of services, calculating the level of logistics services with the subsequent search for the most effective alternatives, the management structure is not only rationalized, it is undergoing some transformation, both of regulations and the complete elimination of direct structural departments of management. In the future, when ubiquitous digital support for management functions only one chief specialist can remain from specialized management services. Therefore, the most important condition for digital transformation at motor transport (MT) enterprises should be integrated control systems based on automation, robotization and digitalization of most processes, which can be delegated to the plane of computerized execution in the field.